A father to love: eros and identification in boys – an emendation of Freud on the male oedipal drama. Issue 1 (2nd January 2016) - Groth, Miles
ABSTRACT: The relationship between a son and his father is usually characterized as primarily one of rivalry. In this emendation of classic oedipal theory, what has traditionally been referred to as the 'negative oedipal relation' is given prominence as a boy's first emotionally significant relationship in which he initiates affection with another human being, his father. Such love is in the service of identification but is also as important as the template for a male's later relationships with women (sexual), other men, and his children. A peculiarity of Freud's relationship with his own father is suggested as the source of oversight of this element of the oedipal drama. A boy's emotional reactive response to his mother is primarily one of gratitude in response to her love. Proactive loving is first experienced with his father.